Financial Ratio Analysis as a Tool for Detecting Financial Statement Misstatements: A Study of Industrial Companies in Indonesia - Chika Meyora Ismanto; Hendra Achmadi (SEAN Institute, 2024)
This study aims to analyze the impact of liquidity ratios, leverage ratios, profitability ratios, asset turnover ratios, and working capital ratios on financial statement misstatements in companies listed on the Indonesia Stock Exchange. The data used is panel data covering 52 companies with two years of observation, namely 2022 and 2023. The regression model used is the random effect model. The results indicate that liquidity ratio (CR) has no significant effect on financial statement misstatements, leverage ratio (DER) has a positive effect on financial statement misstatements, while profitability ratio (ROA) has a negative effect on financial statement misstatements. Furthermore, asset turnover ratio (TATO) and working capital ratio (PER) also have no significant effect on financial statement misstatements. These findings contribute important insights for managerial practice in financial statement management and accounting regulation oversight.